Low-Humidity Sensing Properties of Multi-Layered Graphene Grown by Chemical Vapor Deposition - Ricciardella, Filiberto (Sensors (Basel), 2020)
Humidity sensing is fundamental in some applications, as humidity can be a strong interferent in the detection of analytes under environmental conditions. Ideally, materials sensitive or insensitive towards humidity are strongly needed for the sensors used in the first or second case, respectively. We present here the sensing properties of multi-layered graphene (MLG) upon exposure to different levels of relative humidity. We synthesize MLG by chemical vapor deposition, as shown by Raman spectroscopy, Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). Through an MLG-based resistor, we show that MLG is scarcely sensitive to humidity in the range 30%–70%, determining current variations in the range of 0.005%/%relative humidity (RH) well below the variation induced by other analytes. These findings, due to the morphological properties of MLG, suggest that defective MLG is the ideal sensing material to implement in gas sensors operating both at room temperature and humid conditions.